2020
DOI: 10.1007/s00330-019-06649-z
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound for the characterization of portal vein thrombosis vs tumor-in-vein in HCC patients: a systematic review and meta-analysis

Abstract: Objectives Portal vein thrombosis (PVT) is a common complication of liver cirrhosis. However, differentiation of thrombosis and tumor-in-vein (TIV) may be challenging. Contrast-enhanced ultrasound (CEUS) is an excellent method for detection of vascularization and could help in the distinction. We performed a systematic review and meta-analysis for evaluating the diagnostic value of CEUS in differentiating between PVT and TIV in hepatocellular carcinoma (HCC) patients. Methods PubMed, Embase, Cochrane Library, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
(42 reference statements)
1
20
0
2
Order By: Relevance
“…Interestingly, the LR-TIV and LR-M categories were the most frequent sources of discordant LI-RADS category assignments in our study. Using postoperative pathology as the reference standard, we found that CEUS was more specific than EOB-MRI for diagnosing tumor thrombus (96% vs. 89%, P =.02), which were in line with a recent metaanalysis [31]. This may reflect the higher spatial resolution of CEUS for depicting relatively small vessels as well as its higher temporal resolution for demonstrating the enhancement pattern of the tumor thrombus [32].…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, the LR-TIV and LR-M categories were the most frequent sources of discordant LI-RADS category assignments in our study. Using postoperative pathology as the reference standard, we found that CEUS was more specific than EOB-MRI for diagnosing tumor thrombus (96% vs. 89%, P =.02), which were in line with a recent metaanalysis [31]. This may reflect the higher spatial resolution of CEUS for depicting relatively small vessels as well as its higher temporal resolution for demonstrating the enhancement pattern of the tumor thrombus [32].…”
Section: Discussionsupporting
confidence: 87%
“…Tumor in a vein (LR-TIV) is categorized when the classic arterial hyperenhancement and late mild washout of HCC are seen in soft tissue mass within a vein. A review and subsequent meta-analysis of the diagnostic accuracy of CEUS for diagnosis of a tumor in vein support high sensitivity and specificity from several published studies [31,32] , with a pooled sensitivity of 94% and a pooled specificity of 99%. On the other hand, diagnosis using CT or MRI can be more challenging with a poorer reported performance for more widely available CT/MRI techniques.…”
Section: Description Of the Ceus Li-rads Algorithmmentioning
confidence: 75%
“…In addition, contrast-enhanced ultrasound technology effectively identifies portal vein tumors. [ 13 ] Using this technology, the time of arrival of the contrast agent to the hepatic artery, portal vein, and hepatic vein (HVAT) were recorded. The time interval for the arrival of the contrast agent from the hepatic artery to the hepatic vein (HA-HVAT) and the transit time for the contrast agent to reach the hepatic vein from the portal vein (PV-HVTT) was calculated.…”
Section: Discussionmentioning
confidence: 99%